A Cohort Study Protocol of Low Back Pain In Rural Area Inhabitants: Fasa Low Back Pain Cohort Study (FABPACS): - Farjam, Mojtaba; Askari, Alireza; Hoseinipour, Ali; Homayounfar, Reza; Jamshidi, Javad; Khodabakhshi, Fatemeh; Zakeri, Habib (Galen Medical Journal, 2016)
Background: Low back pain (LBP) is one of the main causes of disability in most societies that imposes much cost to the economic and health systems. In Iranian population, a prevalence as high as 27% has been reported for chronic LBP. So this study was designed to investigate the factors associated with low back pain in Iranian population. Methods/ Design: In Fasa Cohort Study, a branch of Persian cohort study, LBP patients were registered among the participants. A total of 10000 peoples, 1700 patients enrolled in cohort study were registered as LBP patients. In addition to detailed demographic, socioeconomic, anthropometric, nutrition, and medical history, limited physical examinations, determination of physical activity and body composition that was obtained in the cohort study, history of LBP, assessment of the pain severity, McGill pain inventory, and Oswestry questionnaire was filled for the LBP patients. All data are stored online using a dedicated software. Discussion: The cohort study is the best way to collect the necessary information required for policy making in the field of LBP. This study will help in providing some information about LBP in our area to establish a better management of the disease. Moreover, this study will provide many opportunities for clinical trials in this field, and we are going to do interventional studies in the cohort in future.[GMJ.2016;5(4):225-29]